Understanding How Surgeons Improve the Quality of Breast Cancer Surgery Using the Theoretical Domains Framework - Doris Goubran, BHSc; Iresha Ratnayake, MSc; Pamela Hebbard, MD, FRCSC; Caroline Park, BN, Med, PhD; Maziar Fazel Darbandi, MD; Kathleen Decker, PhD; Megan Delisle, MD, MPH, MSc, FRCSC (Annals of Surgery Open)
Objective:. To understand how surgeons improve the quality of breast cancer surgery. Background:. Between 2007 and 2021, breast cancer surgeons in Manitoba, Canada, participated in national initiatives to build a local capacity for quality improvement (QI) in cancer surgery. Key aspects of these initiatives include audit and feedback reports using data from synoptic operative reports and communities of practice. Surgeon engagement in breast cancer surgery QI in Manitoba has not been evaluated since the initiatives were concluded in 2021. Methods:. We conducted 60-minute virtual semi-structured qualitative interviews with surgeons who performed breast cancer surgery in Manitoba, Canada, between 2021 and 2024. The interviews were guided by the theoretical domain framework. The thematic analyses were performed by 2 independent researchers. Results:. Twelve surgeons were interviewed. Surgeons were motivated to ensure timely care close to home, with excellent oncological, surgical, and aesthetic outcomes. They felt capable of monitoring and improving their surgical quality by tracking their own metrics, collaborating with multidisciplinary colleagues, engaging in continuous professional development, and advocating for improvement. Audit and feedback reports were not perceived to improve the quality of surgery. They felt limited opportunities to sustain improvement strategies. Resource constraints and leadership support within the healthcare system were major barriers to achieving their ideal quality of care. Conclusion:. Surgeons performing breast cancer surgery in Manitoba were motivated and capable of improving the quality of breast cancer surgery. However, they perceive limited opportunities and barriers within the healthcare systems to doing so. Future research will provide information on broader contextual factors affecting breast cancer surgery QI.